2018
DOI: 10.3390/ma11040462
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a New Dental Implant Cervical Design in Comparison with a Conventional Design in an Experimental American Foxhound Model

Abstract: The aim of this study was to evaluate osseointegration and crestal bone height in implants with a triangular cervical design in comparison with a standard rounded cervical design. The control group consisted of 24 implants with a standard cervical design, and the test group of 24 implants with a triangular cervical design. The implants were inserted in healed bone in six American Foxhounds. Crestal bone height and tissue thickness in the cervical portion were measured after 12 weeks healing. Data analysis foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 36 publications
(39 reference statements)
0
10
0
Order By: Relevance
“…Several studies about implant neck design and marginal bone loss can be found in the literature, but the results are controversial. In vivo animal studies reported a greater crestal bone height and thickness of surrounding implant tissue in dental implants with triangular neck designs [8]; smaller crestal bone loss but similar peri-implant tissue thickness in narrow ring extra-shorts implants [9]; and greater bone loss in dental implants with micro-rings on the neck, as compared to open-thread implant collars [10]. Human model studies reported improved biomechanical behavior for stress/strain distribution pattern in dental implants with divergent collar design [11]; no additional bone loss in non-submerged dental implants with a short smooth collar compared to similar but longer implant collar design [12].…”
Section: Introductionmentioning
confidence: 98%
“…Several studies about implant neck design and marginal bone loss can be found in the literature, but the results are controversial. In vivo animal studies reported a greater crestal bone height and thickness of surrounding implant tissue in dental implants with triangular neck designs [8]; smaller crestal bone loss but similar peri-implant tissue thickness in narrow ring extra-shorts implants [9]; and greater bone loss in dental implants with micro-rings on the neck, as compared to open-thread implant collars [10]. Human model studies reported improved biomechanical behavior for stress/strain distribution pattern in dental implants with divergent collar design [11]; no additional bone loss in non-submerged dental implants with a short smooth collar compared to similar but longer implant collar design [12].…”
Section: Introductionmentioning
confidence: 98%
“…Recently, non‐circular cross section implant designs were introduced by several companies in order to leave more space for bone apposition (Nevins et al, 2020), to allow a better force dissipation in the region of the crestal bone (Zanatta et al, 2014) and potentially improve peri‐implant bone stability when compared to classical round neck implant designs. Preclinical studies showed conflicting results: some studies suggested that triangular neck implants allow a greater thickness of peri‐implant tissue while others did not find any differences in terms of buccal bone volume and soft tissues contours (Pérez‐Albacete Martínez et al, 2018; Sanz‐Martin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated evidence suggests that both the stability of crestal bone levels and peri‐implant soft tissue are crucial for the long‐term success of an implant (Simonis et al, 2010; Srinivasan et al, 2016). Hence, there is increased interest from dental practitioners in preserving crestal bone levels around implants, which appears to be an important prerequisite for a successful longer‐term treatment outcome (Al‐Zordk et al, 2020; Amid et al, 2013; Bateli et al, 2011; Broggini et al, 2006; Eshkol‐Yogev et al, 2019; Li Manni et al, 2020; Maeda et al, 2007; Norton & Åström, 2020; Pérez‐Albacete Martínez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…bone levels around implants, which appears to be an important prerequisite for a successful longer-term treatment outcome (Al-Zordk et al, 2020;Amid et al, 2013;Bateli et al, 2011;Broggini et al, 2006;Eshkol-Yogev et al, 2019;Li Manni et al, 2020;Maeda et al, 2007;Norton & Åström, 2020;Pérez-Albacete Martínez et al, 2018).…”
mentioning
confidence: 99%